Proceedings of the Ecological-Socio-Economic Systems: Models of Competition and Cooperation (ESES 2019) 2020
DOI: 10.2991/assehr.k.200113.019
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Rural Territories According to the Conditions of Human Reproduction

Abstract: In conditions of high spatial differentiation of rural territories, an objective assessment of the conditions for the reproduction of human capital is of particular importance. However, the developed methods, firstly, cannot always take into account all the components of human capital. Secondly, they do not affect the conditions for its accumulation. Thirdly, they include various indicator systems that are difficult to interpret when analyzing. In this regard, the results of such assessments lead to significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The calculation of the final score and the ranking of macroregions based on it showed that the best conditions for the reproduction of human capital were created in the rural territories of the Ural-Siberian and Far Eastern macro-regions, where the Yamalo-Nenets and Chukotka Autonomous Districts can be distinguished. The Angara-Yenisei macro-region and especially the Republic of Tuva have worse conditions [17].…”
Section: Human Capital Level Conditions For Forming Human Capitalmentioning
confidence: 99%
“…The calculation of the final score and the ranking of macroregions based on it showed that the best conditions for the reproduction of human capital were created in the rural territories of the Ural-Siberian and Far Eastern macro-regions, where the Yamalo-Nenets and Chukotka Autonomous Districts can be distinguished. The Angara-Yenisei macro-region and especially the Republic of Tuva have worse conditions [17].…”
Section: Human Capital Level Conditions For Forming Human Capitalmentioning
confidence: 99%